Synthesis and Characterization of TEOS-based Materials for Hydrophobic Corrosion Protection as Silica - Irpansyah Siregar; Jon Affi; Yuli Yetri; Hariyati Lubis; Tengku Machdhalie Sofie (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2026)
This research prepared superhydrophobic protection based on tetraethyl orthosilicate (TEOS) as a silica substitute using the sol-gel method. The raw material involved sodium silicate, TEOS, cetyltrimethylammonium bromide (CTAB) surfactant, and trimethylammonium chloride (TMACl). Characterization techniques employed include Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy (SEM-EDS), X- Ray Fluorescence (XRF), and X-Ray Diffraction (XRD). According to the XRD analysis, a characteristic diffraction peak of silica was observed at 2θ = 31.680°. The SEM results revealed a uniform surface morphology, attributed to the homogeneous grinding process during sample preparation. The EDS investigation exhibited the elemental compositions of Si, Fe, O, Cl, and C. The XRF analysis confirmed the presence of silicon (Si), originating from TEOS, which was used as the silica source. The water contact angle test shows sample with 10% TEOS has highest angles as 50. 56 degree.